2015
DOI: 10.1111/mmi.13206
|View full text |Cite
|
Sign up to set email alerts
|

BadR (BB0693) controls growth phase‐dependent induction of rpoS and bosR in Borrelia burgdorferi via recognizing TAAAATAT motifs

Abstract: SummaryIn Borrelia burgdorferi (Bb), the alternative sigma factor RpoS plays a central role during Bb's adaptation to ticks and mammals. Previous studies have demonstrated that RpoS is not expressed during the early stages of spirochetal growth or when Bb resides in ticks during the intermolt phase, but the molecular details of these events remain unknown. In the current study, biomagnetic bead separation of rpoS promoter-binding proteins, coupled with genetic inactivation, was employed to identify BadR (BB069… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 103 publications
(239 reference statements)
1
53
0
Order By: Relevance
“…Previously, we (58) and others (60) reported that BadR negatively influences rpoS expression by binding to the rpoS promoter. Furthermore, our previous data indicated that badR is also highly expressed in ticks during the acquisition and intermolt phases (58). Therefore, high levels of BadR may occupy the rpoS promoter region, which could inhibit the recruitment of BosR, 54 (RpoN), and Rrp2 to the rpoS promoter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we (58) and others (60) reported that BadR negatively influences rpoS expression by binding to the rpoS promoter. Furthermore, our previous data indicated that badR is also highly expressed in ticks during the acquisition and intermolt phases (58). Therefore, high levels of BadR may occupy the rpoS promoter region, which could inhibit the recruitment of BosR, 54 (RpoN), and Rrp2 to the rpoS promoter.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were then loaded onto a 12.5% acrylamide gel. The resolved proteins were either stained with Coomassie brilliant blue R-250 or electrotransferred onto a nitrocellulose membrane for immunoblot analysis as previously described (37,58). BosR, RpoS, and OspC were detected using antiBosR polyclonal antibody (38), anti-RpoS monoclonal antibody 6A7-101 (26), or anti-OspC monoclonal antibody 1B2-105A (59), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this pathway, the two-component system Hk2-Rrp2 activates the σ N –σ S (RpoN-RpoS) sigma factor cascade, leading to the production of σ S (RpoS), which in turn, controls expression of many virulence genes including ospC and many other genes (for review, see, Samuels, 2011; Radolf et al, 2012; Ouyang et al, 2014; Ye et al, 2016b). In addition, many other factors including BosR (Hyde et al, 2009; Ouyang et al, 2009, 2011), BadR (Miller et al, 2013; Ouyang and Zhou, 2015), DsrA (Lybecker and Samuels, 2007), Rrp1 (Rogers et al, 2009; Sze et al, 2013; He et al, 2014), BtmA (Troxell et al, 2013), SodA (Esteve-Gassent et al, 2015), BBD18 (Dulebohn et al, 2014), also influence rpoS and ospC expressions.…”
Section: Introductionmentioning
confidence: 99%
“…We postulate that under the RpoN-RpoS on conditions, both Rrp2-P and BosR are present, whereas under the RpoN-RpoS off conditions, Rrp2-P is present, but BosR is not. Indeed, the level of BosR was shown to be consistent with the production of RpoS under in vitro cultivation conditions (10,14,33).…”
Section: Discussionmentioning
confidence: 90%
“…RpoS, functioning as a global regulator, further controls the expression of numerous genes important for the enzootic cycle of B. burgdorferi (for a review, see references 2, 3, and 9). Since the first discovery of this pathway, additional factors, including BosR (10)(11)(12), BadR (13,14), DsrA (15), Rrp1 (16)(17)(18), and the posttranscriptional regulation of rpoS (19), have been identified.…”
mentioning
confidence: 99%